Examining the Impact of Treatment Fidelity on Client Outcomes in a Statewide Implementation of Parent-Child Interaction Therapy. Issue 3 (3rd July 2021) - Snider, Mira D. H.; Herschell, Amy D.; Jackson, Carrie B.; Funderburk, Beverly W.; Schaffner, Kristen F.; Taber-Thomas, Sarah; Kolko, David J.
Abstract: Treatment fidelity, including adherence and competence, is assessed during the implementation of evidence-based treatments to ensure that care is delivered as intended. Although fidelity monitoring is often resource-intensive, a relationship between fidelity and treatment outcomes has not been clearly demonstrated. Associations between observer-rated clinician fidelity and family treatment outcomes were investigated in a longitudinal sample of clinicians ( n = 18) and parent-child dyads ( n = 39) following a statewide implementation of Parent-Child Interaction Therapy. Results indicated that neither adherence nor coaching competence predicted changes in treatment outcomes. Explanations for these findings, study limitations, and directions for future research are discussed.